N‐methyl‐d‐aspartate receptor mediated calcium influx supports in vitro differentiation of normal mouse megakaryocytes but proliferation of leukemic cell lines. Issue 1 (14th December 2017) - Kamal, Tania; Green, Taryn N.; Hearn, James I.; Josefsson, Emma C.; Morel‐Kopp, Marie‐Christine; Ward, Christopher M.; During, Matthew J.; Kalev‐Zylinska, Maggie L.
Abstract: Essentials Intracellular calcium pathways regulate megakaryopoiesis but details are unclear. We examined effects of NMDAR‐mediated calcium influx on normal and leukemic cells in culture. NMDARs facilitated differentiation of normal but proliferation of leukemic megakaryocytes. NMDAR inhibitors induced differentiation of leukemic Meg‐01 cells. Background: N ‐methyl‐d ‐aspartate receptors (NMDARs) contribute calcium influx in megakaryocytic cells but their roles remain unclear; both pro‐ and anti‐differentiating effects have been shown in different contexts. Objectives: The aim of this study was to clarify NMDAR contribution to megakaryocytic differentiation in both normal and leukemic cells. Methods: Meg‐01, Set‐2, and K‐562 leukemic cell lines were differentiated using phorbol‐12‐myristate‐13‐acetate (PMA, 10 nmol L −1 ) or valproic acid (VPA, 500 μmol L −1 ). Normal megakaryocytes were grown from mouse marrow‐derived hematopoietic progenitors (lineage‐negative and CD41a‐enriched) in the presence of thrombopoietin (30‐40 nmol L −1 ). Marrow explants were used to monitor proplatelet formation in the native bone marrow milieu. In all culture systems, NMDARs were inhibited using memantine and MK‐801 (100 μmol L −1 ); their effects compared against appropriate controls. Results: The most striking observation from our studies was that NMDAR antagonists markedly inhibited proplatelet formation in all primary cultures employed. Proplatelets were either absent (in the presence of memantine) or short, broad and intertwined (with MK‐801). Earlier steps of megakaryocytic differentiation (acquisition of CD41a and nuclear ploidy) were maintained, albeit reduced. In contrast, in leukemic Meg‐01 cells, NMDAR antagonists inhibited differentiation in the presence of PMA and VPA but induced differentiation when applied by themselves. Conclusions: NMDAR‐mediated calcium influx is required for normal megakaryocytic differentiation, in particular proplatelet formation. However, in leukemic cells, the main NMDAR role is to inhibit differentiation, suggesting diversion of NMDAR activity to support leukemia growth. Further elucidation of the NMDAR and calcium pathways in megakaryocytic cells may suggest novel ways to modulate abnormal megakaryopoiesis.